Reduced heart rate variability is related to fluctuations in psychological stress levels in daily life - Kim, Jinhyuk; Foo, Jerome Clifford; Murata, Taiga; Togo, Fumiharu (Stress and health, 2024)
Laboratory-based studies have shown that psychological stress caused by response to various stressors triggers acute changes in the cardiovascular system. A better understanding is needed of the emerging evidence on temporal associations between psychological stress and cardiovascular responses in natural settings. This study examined the association of psychological stress and heart rate variability (HRV) in daily life, at high resolution over 2 weeks, taking the effect of physical activity into account. Participants (n = 34) completed ecological momentary assessments (EMA) 6 times per day, reporting levels of perceived stress, low-arousal negative affect (LNA), and high-arousal negative affect. Chest-mounted heart-rate monitors were worn to assess HRV. Multilevel models were used to examine the association between psychological stress levels and preceding/subsequent HRV. Reduced time domain HRV measures (mean and standard deviation of R-wave to R-wave intervals) during the prior hour predicted higher levels of perceived stress. Frequency domain HRV measures higher low to high frequency (LF/HF) and lower HF to total power (HF nu) ratios during the preceding 10 min predicted higher perceived stress levels, suggesting the dominance of sympathetic nervous system activity. EMA reports of higher perceived stress levels were associated with reduced time domain HRV measures during the following 10 min. On the other hand, higher LNA were related to increased HRV measures, such as lower LF/HF and higher HF nu during the following hour. The dynamic associations observed may have therapeutic implications for ‘just-in-time’ interventions in the management of daily stress and cardiovascular health.
Erstmals veröffentlicht: 20. Juli 2024
Gesehen am 18.11.2024